PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN RADEC DI KELAS IV SDN 09 RANAH BATAHAN - Fitri, Riza Amalia; S, Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe the improvement in learning outcomes using the RADEC learning model in class IV SDN 09 Ranah Batahan. This research is classroom action research (PTK) using qualitative and quantitative approaches. Two cycles were carried out, where cycle I consisted of 2 meetings and cycle II consisted of 1 meeting. Data from the research were obtained from the Teaching Module assessment, implementation process, and learning outcomes. The data collection technique uses test and non-test data collection techniques. The results of the research show an increase in: a) Teaching Module cycle I with an average of 90% (very good) and cycle II 97.5% (very good), b) Implementation in aspects first cycle teachers with an average of 82.14% (good) and second cycle 96.42% (very good), while implementation in the student aspect of first cycle with an average of 85.71% (good) and second cycle 96.42% c) The assessment of students in improving learning outcomes in cycle I was obtained with an average of 80.73 and in cycle II with an average of 92.55. Based on these results, it can be concluded that the RADEC model can improve student learning outcomes in natural and social science learning.